Trogocytosis at the crossroad of cancer and immunity: mechanisms, implications and therapeutic perspectives - Guha, Aishwarya; Banerjee, Saptak (Frontiers in Cell and Developmental Biology, 2025)
Trogocytosis, a rapid and contact-dependent exchange of plasma membrane fragments and associated molecules between cells, has recently emerged as a critical but underappreciated player in cancer biology. Traditionally studied in the context of immune cell communication, trogocytosis is now recognized for its paradoxical role in modulating tumor progression and therapeutic response across a broad spectrum of malignancies. This review highlights the novel and dynamic functions of trogocytosis in shaping the tumor microenvironment (TME), promoting immune evasion and influencing metastatic potential. Notably, cancer cells exploit trogocytosis to acquire immune regulatory molecules such as CD45, CD4 and checkpoint proteins, effectively dampening anti-tumor responses while enhancing their own survival. Simultaneously, immune effector cells including macrophages, T cells and natural killer (NK) cells leverage trogocytosis to recognize, attack and even kill tumor cells through mechanisms such as trogoptosis. Compelling new evidence also links trogocytosis to therapeutic resistance, particularly in chimeric antigen receptor (CAR-T and CAR-NK) cell therapies, where tumor antigens like CD19 and CD22 are siphoned off by effector cells, leading to T cell fratricide, functional exhaustion and tumor relapse. Beyond its biological significance, trogocytosis is gaining attention as a translational tool in oncology. It offers a novel platform for antigen-specific drug delivery, spatially restricted immune modulation and biomarker discovery through the detection of trogocytosed molecules on circulating immune-cells or extracellular vesicles. These findings redefine trogocytosis as not merely a passive membrane exchange process, but a central mechanism of intercellular communication with profound implications for cancer progression, immunotherapy and precision medicine.